Getting to the Source: Selective Drug Targeting of Cancer Stem Cells. Issue 5 (23rd April 2014) - Ismail, Fatima; Winkler, David A.
Abstract Cancers are among the most important and most difficult to treat diseases of the 21st century. Conventional therapies include surgery, immunotherapy, and radiotherapy, as well many forms of drug treatments such as tamoxifen and Gleevec. However, these forms of treatment often do not eradicate the cancer stem cells, only managing to decrease the size of the tumor, allowing the cancer to return. The cancer stem cell hypothesis stipulates that malignancy is maintained through self‐renewal of cancer stem cells (CSCs), which generate rapidly dividing progeny that comprise the tumors, and that are largely untouched by conventional therapies. Evidence for the central role of CSCs in many tumors has provided a paradigm shift in the way cancer chemotherapy may be addressed. Recent discoveries regarding the nature of the stem cell niche, and the key signaling pathways involved in stem cell self‐renewal and differentiation from regenerative medicine, have provided key information that facilitates selective targeting of CSCs by small‐molecule drugs. The growing body of biochemical knowledge on the nature of CSCs, and differences between them and normal adult stem cells essential for maintaining organisms, has augmented the increasing number of small molecules shown to control normal and aberrant stem cells. Here, we review small‐molecule approaches to the selective targeting of CSCs.